The relationship between stress levels and sleep quality on blood pressure among medical student - Hafizhah, Dhea; Delfian, Taufik; Budi, Andre (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2024)
Hypertension, often termed a